Literature Review Study: Learning Model for Indonesian Language Lectures - Yani, Ahmad (JUPE : Jurnal Pendidikan Mandala, 2025)
This research seeks to explore different learning models employed in Indonesian language classes via a literature review. The approach entails performing a structured search of the Google Scholar database utilizing terms like "learning models," "Indonesian language education," and "teaching methods." Research articles concentrate on learning the Indonesian language in higher education were chosen for examination. This study examined nine research articles that highlighted various learning models applicable in Indonesian language classes. These models consist of online learning approaches that focus on collaboration and courtesy, problem-focused learning models, project-oriented learning models, seminar simulation learning models, multiliteracy educational models, and jigsaw methods grounded in lesson study. The research finds that utilizing various learning models improves the efficiency of Indonesian language teaching; nevertheless, there is a need for improved alignment with student requirements and technological progress. Additional studies are suggested to create models that are better aligned with the context of contemporary education.